2013
DOI: 10.1186/1471-227x-13-3
|View full text |Cite
|
Sign up to set email alerts
|

Advanced accident research system based on a medical and engineering data in the metropolitan area of Florence

Abstract: BackgroundIn the metropolitan area of Florence, 62% of major traumas involve powered two wheeler rider and pillion passengers, 10% cyclists, and 7% pedestrians. The urban and extra-urban areas are the most dangerous for the vulnerable road user. In-depth investigations are needed for assessing detailed information on road accidents. This type of study has been very limited in time frame in Italy, and completely absent in the Tuscan region.Consequently a study called “In-depth Study of road Accident in FlorencE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…The second experiment analyzed a pre-crash scenario (pre-crash test) and consisted in emulating the trajectories of a scooter and a car that led to a documented crash [ 108 , 109 ]. The aim of this experiment was to assess whether the sensors under test can sense the changing traffic scene at least 1 s before the collision becomes inevitable.…”
Section: Test Protocolsmentioning
confidence: 99%
“…The second experiment analyzed a pre-crash scenario (pre-crash test) and consisted in emulating the trajectories of a scooter and a car that led to a documented crash [ 108 , 109 ]. The aim of this experiment was to assess whether the sensors under test can sense the changing traffic scene at least 1 s before the collision becomes inevitable.…”
Section: Test Protocolsmentioning
confidence: 99%
“…The In-depth Study of road Accidents in Florence (InSAFE) team has been carrying out in-depth road accident studies in the metropolitan area of Florence since 2009 (Piantini et al 2013). The investigated crashes must have occurred in the metropolitan area of Florence and have involved at least one seriously injured person.…”
Section: Italymentioning
confidence: 98%
“…First, a suitable set of case studies were identified from a subset of cases extracted from InSAFE, the in-depth crash investigation database active in the area of Florence, Italy [4]. The criteria for a case to be considered in the study were the following: i) PTW colliding against another vehicle (car or van); ii) a 2D reconstruction of the vehicles' trajectories was available; iii) according to the results of a previous study [2], MAEB would have applied.…”
Section: Selection Of the Case Studymentioning
confidence: 99%